Approximation of Certain Classes of Singular Integrals by Algebraic Polynomials - Motornyi, V. P.; Моторный, В. П.; Моторный, В. П. (Institute of Mathematics, NAS of Ukraine, 2001)
We study the problem of pointwise approximation by algebraic polynomials for classes of functions that are singular integrals of bounded functions. We obtain asymptotically exact estimates of approximations.